2019
DOI: 10.1039/c9fo01730e
|View full text |Cite
|
Sign up to set email alerts
|

Roles of different n-3/n-6 PUFA ratios in ovarian cell development and steroidogenesis in PCOS rats

Abstract: Polycystic ovary syndrome (PCOS) is a complex and common endocrine disorder characterized by hyperandrogenism, which is accompanied by follicle growth arrest at the small antral stage, minimal granulosa cell proliferation, and chronic anovulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…hs-CRP is a biochemical marker produced in response to stimulation by IL, such as IL-6 (43) , which can be downregulated by EPA and DHA (38,39) . With regard to serum n-3 PUFA, we found that the levels of LH decreased as the levels of total, certain long-chain n-3 PUFA, EPA, DPA and DHA increased, while the levels of FSH and SHBG increased when all the serum n-3 PUFA mentioned above increased, except for ALA. PUFA may induce elevated serum FSH due to the upregulated expression of cytochrome P450 lanosterol 14a-demethylase (CYP51), a critical enzyme that converts lanosterol into cholesterol, in granulosa cells (44,45) .…”
Section: Discussionmentioning
confidence: 99%
“…hs-CRP is a biochemical marker produced in response to stimulation by IL, such as IL-6 (43) , which can be downregulated by EPA and DHA (38,39) . With regard to serum n-3 PUFA, we found that the levels of LH decreased as the levels of total, certain long-chain n-3 PUFA, EPA, DPA and DHA increased, while the levels of FSH and SHBG increased when all the serum n-3 PUFA mentioned above increased, except for ALA. PUFA may induce elevated serum FSH due to the upregulated expression of cytochrome P450 lanosterol 14a-demethylase (CYP51), a critical enzyme that converts lanosterol into cholesterol, in granulosa cells (44,45) .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies have confirmed the reliability of metabolic changes in assessing oocyte quality and studying ovarian diseases. 9,10 We therefore analysed the fecal metabolic profiles using UHPLC-Q-TOF-MS/MS. The results of the partial least squares discriminant analysis (PLS-DA) score plot showed that the quality control samples were well clustered in both positive and negative ion modes (Fig.…”
Section: Effects Of Lbp Supplementation On the Fecal Metabolite Profi...mentioning
confidence: 99%
“…7 Studies have shown that a variety of metabolites, including lipids, glycerophospholipids, steroids and amino acids, are altered in POI patients. 8 Early studies have confirmed the reliability of metabolic changes in assessing oocyte quality and studying ovarian diseases, 9,10 suggesting that metabolic changes may provide a suitable strategy for POI research.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the balanced diet, supplementation can be regarded as a seasonal intervention [ 112 ]. Polyunsaturated fatty acids (PUFAs) enhance the reproductive performance in PCOS by increasing the expression of steroidogenesis enzymes, which are related to hormone secretion and ovarian functions, and the protein levels of CYP51, CYP19, StAR, and 3β-HSD [ 113 ]. In summary, supplementing the diet is an individual subject that requires dietary consultation with the patient, and its active participation and compliance is desirable for the overall improvement of the metabolic equilibrium.…”
Section: Lifestyle Changesmentioning
confidence: 99%